AI-Driven Cyber Threat Detection and Prevention Systems - Rakhi Thakur, (Journal of Computational Analysis and Applications (JoCAAA), 2024)
The increasing complexity and frequency of cyberattacks in today’s interconnecteddigital environment have outpaced the capabilities of traditional security mechanisms. To addressthese evolving threats, Artificial Intelligence (AI) has emerged as a transformative technology in cybersecurity.